MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN SOSIAL MAHASISWA - Ayu Faiza Algifahmy (Universitas Islam Sultan Agung, 2019)
The CIRC (Cooperative Integrated Reading and Composition) learning model is a comprehensive learning program to teach reading and writing to students used in each course in the History of Islamic Civilization. This study aims to determine the effect of the CIRC learning model of learning outcomes of cognitive aspects of students in the History of Islamic Civilization course at the Faculty of Da'wah and Communication. This research is an experimental research. The population in this study are students of the History of Islamic Civilization course, so it can be concluded that the average group learning outcomes will be better. The purpose of this study is to describe the application of the CIRC method in improving students' social abilities and describing their improvement. Based on these results, it can be concluded that the application of the CIRC method can improve social skills and read students' understanding.Keywords: CIRC method, social ability, student